Comparison Of King's Clinical Staging In Multinational Amyotrophic Lateral Sclerosis Cohorts. Issue 1 (2nd January 2023) - Balendra, Rubika; Jones, Ashley R.; Al Khleifat, Ahmad; Chiwera, Theresa; Wicks, Paul; Young, Carolyn A.; Shaw, Pamela J.; Turner, Martin R.; Leigh, P. Nigel; Al-Chalabi, Ammar
Abstract: Background : Amyotrophic lateral sclerosis (ALS) shows considerable clinical heterogeneity, which affects clinical trials. A clinical staging system has been proposed for ALS with potential applications in patient care, research, trial design and health economic analyses. The King's system consists of five stages. We have previously shown that progressive clinical stages were reached at predictable proportions through the disease course, but this needs to be validated in other independent samples. Objectives : We aimed to compare King's clinical staging in ALS in four patient groups, located in different regions and countries and using different health care systems from the original study population in South London. Methods : Clinical data were extracted from two European phase 3 randomized controlled trials (MitoTarget and LiCALS) and from two databases predominately from the United States: the PRO-ACT Consortium Database and a database of patients from the PatientsLikeMe website. Clinical stage was estimated using an algorithm, and standardized time to each clinical stage was calculated in deceased patients. Results : 8, 796 patients were included, of whom 1, 959 had died by the end of follow-up. Stages occurred in the same order as in the original study for all cohorts. Median standardized times to stages (interquartile range) were Stage 2: 0.61 (0.47–0.75), Stage 3: 0.68 (0.56–0.81), Stage 4A: 0.82 (0.71–0.91), Stage 4B: 0.82 (0.69–0.92) and Stage 4 0.80 (0.67–0.91). Discussion : Timings for all stages were similar to those reported in the original study, except Stage 2 which occurred later in the clinical trial databases due to recruitment occurring after diagnosis.